(untitled) (Bangladesh Journal of Agricultural Research, 2012)
A study was carried out to find out the effect of sowing dates and varieties on the severity of Alternaria blight of mustard. Seeds of eight mustard varieties were sown on four different dates. Data on severity of the disease and seed yield were recorded. Disease severity differed significantly among the varieties. B. campestris varieties showed the higher disease severity compared to B. napus and B. juncea. The lowest disease severity was recorded in BARI Sarisha 11 which produced the highest seed yield. Percentages of leaf area diseased, leaf infection, siliqua infection, and spots per siliqua were found lowest under 21 October sowing, which were statistically lower than other sowing dates. The highest seed yield (1727 kg/ha) was recorded under 01 November sowing followed by 21 October sowing. Combination of sowing dates and varieties had a significant influence on disease severity and seed yield. Early sown (21 October and 1 November) BARI Sarisha 11 showed less disease severity and gave higher seed yield than other treatment combinations DOI: http://dx.doi.org/10.3329/bjar.v36i4.11746 Bangladesh J. Agril. Res. 36(4): 583-594, December 2011